Residential electricity package model considering load difference penalty in China - Zhou, Xiuna; Dong, Junfeng; Wang, Gang; Chu, Yan (Frontiers in Energy Research, 2023)
The increasing load difference between peak and off-peak seasons has led to the unstable operation of China’s power systems in recent years. In addition, the current electricity package structure system of China, which is gradually liberalizing its electricity market, remains imperfect. This study proposes a model of residential electricity packages that considers load difference penalty during peak and off-peak seasons. First, the utility of different packages to users is analyzed, and the best package is selected by maximizing the utility function. Then, a load difference minimization model of retail electricity packages during peak and off-peak seasons is established and optimized using the particle swarm algorithm. Finally, on the basis of the simulation results of the example, users are encouraged to use electricity reasonably and load difference between peak and off-peak seasons is reduced. The profit of retailers is increased to a certain extent. A comparative analysis disregards the penalty for load difference and establishes a model of packages with the maximization of retailers’ profit as the optimization objective. A retailer obtains higher profits and reduces load difference between peak and off-peak seasons to a certain extent.